Hadith #5473 - Sahih al-Bukhari - Khalid bin Sa'd al-Kwfy خالد بن سعد الكوفي (Sahih al-Bukhari)
We went out and Ghalib bin Abjar was accompanying us. He fell ill on the way and when we arrived at Medina he was still sick. Ibn Abi ‘Atiq came to visit him and said to us, “Treat him with black cumin. Take five or seven seeds and crush them (mix the powder with oil) and drop the resulting mixture into both nostrils, for `Aisha has narrated to me that she heard the Prophet (ﷺ) saying, ‘This black cumin is healing for all diseases except As-Sam.’ Aisha said, ‘What is As-Sam?’ He sa
Grade: Sahih

Hadith #2181 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Ahmed bin Suliaman أحمد بن سليمان; Aisha bint Abi Bakr; Khalid bin Sa'd al-Kwfy خالد بن سعد الكوفي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“The Messenger of Allah used to join Shaban to Ramadan.” ‘
Grade:

Hadith #2363 - Sunan al-Nasa'i - Abu Da'ud أبو داود السجستاني الأزدي; Ahmed bin Suliaman أحمد بن سليمان; Aisha bint Abi Bakr; Khalid bin Sa'd al-Kwfy خالد بن سعد الكوفي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan al-Nasa'i)
“I said: ‘O Messenger of Allah, sometimes you fast, and you hardly ever break your hardly ever fast, except two days which, if you are fasting, you include them in your fast, and if you are not fasting, then you fast them on your own.’ He said: ‘Which two days?’ I said: ‘Monday and Thursday.’ He said: ‘Those are two days in which deeds are shown to the Lord of the worlds, and I like my deeds to be shown (to Him) when I am fasting.”‘
Grade:

Hadith #5703 - Sunan al-Nasa'i - Abu Mas'ud al-Badri; Khalid bin Sa'd al-Kwfy خالد بن سعد الكوفي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Yahya bin Yaman al-Jly يحيى بن يمان العجلي (Sunan al-Nasa'i)
“I asked Ibn ‘Abbas: ‘I have a small jar in which I make Nabidh and when it has bubbled and settled down again, I drink it.’ He said: ‘For how long you have been drinking that?’ He said: ‘For twenty years'” – or he said: ‘for forty years.’ He said: ‘For a long time you have been quenching your thirst with something forbidden.'”
Grade:

Hadith #3573 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Khalid bin Sa'd al-Kwfy خالد بن سعد الكوفي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Ibn Majah)
“I asked ‘Aishah about a supplication that the Messenger of Allah (saas) used to say. She said that he used to say: ‘Allahumma inni a’udhu bika min sharri ma ‘amiltu, wa min sharri ma lam a’mal (O Allah, I seek refuge with You from the evil of that which I have done and the evil of that which I have not done).'”
Grade: